1993
DOI: 10.1007/bf00166950
|View full text |Cite
|
Sign up to set email alerts
|

Positive inotropic action of angiotensin II in the pithed rat

Abstract: The cardiovascular effects of angiotensin II were examined in aortic blood pressure-controlled and -uncontrolled pithed rats. Angiotensin II induced a dose-dependent increase in diastolic blood pressure, left ventricular pressure (LVP), dP/dt (the first derivative of LVP) and heart rate in pithed rats. The maximal responses for these parameters were similar to those to noradrenaline, except for the rise in diastolic blood pressure, where noradrenaline caused a greater increase than angiotensin II. After treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…It has been demonstrated that All can cause positive inotropic effects in rats (Zhang et al, 1993) and other species (Lindpaintner & Garten, 1991). However, in isolated right atria preparations, we observed that All, AIII and AIV slightly decreased the amplitude of beating simultaneously with the increases in frequency.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…It has been demonstrated that All can cause positive inotropic effects in rats (Zhang et al, 1993) and other species (Lindpaintner & Garten, 1991). However, in isolated right atria preparations, we observed that All, AIII and AIV slightly decreased the amplitude of beating simultaneously with the increases in frequency.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous investigations in our department (Knape & van Zwieten, 1988;Zhang et al, 1993) have shown that the tachycardic response induced by All in the pithed rat is generated by a direct positive chronotropic effect as well as by an indirect action of All, which is known to stimulate the sympathetic ganglia, thus leading to the release of catecholamines. It has also been found (Allen et al, 1988) that All increases the spontaneous contractile frequency in cultured heart myocytes from neonatal rats.…”
Section: Introductionmentioning
confidence: 96%
“…In this respect, one possibility that this study did not explore is the potential interference of palmitoylethanolamide with the RAAS, in view that in pithed rats a proportion of blood pressure seems to be maintained by activation of the RAAS, as reported by Schlicker et al [30]. Consistent with this possibility, infusions of angiotensin II produce tachycardic and vasopressor responses [33,34]. Clearly, this is a hypothetical speculation that requires other experimental approaches that include the use of i.v.…”
Section: Changes On Systemic Haemodynamic Variables Produced By the Dmentioning
confidence: 68%
“…Glucose clamp experiments employed the pithed rat preparation, which is well established as a model for peripheral cardiovascular regulation, given that central neural reflex mechanisms have been eliminated (Gillespie & Muir, 1967; Zhang et al, 1993). We used it in order to remove possible direct neural influences on pancreatic function.…”
Section: Methodsmentioning
confidence: 99%